Effects of the COVID-19 pandemic on Vocational Education and Training. A best practice example: lecturer development project TRAINME - Adam, Carina [Verfasser] (My University, 2022)
"Not only did COVID-19 have an impact on Vocational Training in the TVET colleges directly but also on continuous professional development of the lecturers. Classes had to be held online; distance learning and remote teaching were the buzzwords. An entirely new structure had to be designed, both for teach ing and learning. TRAINME is a BMBF-funded project for further education of South African TVET lecturers that was hit by the pandemic in the middle of the programme. The project reacted to challenges with great flexibility and substituted large parts of the training with virtual offers." (Author's abstract ; BIBB-Doku)
Keywords: I 2.3.1 Afrika; L 4.2 Mediengestützte Lehr-Lernformen; 370; Berufsausbildung; Weiterbildung; Pandemie; Südafrika; Maschinenbau; Elektrotechnik; Blended learning